2022
DOI: 10.1038/s41598-022-08889-4
|View full text |Cite
|
Sign up to set email alerts
|

Female hormones prevent sepsis-induced cardiac dysfunction: an experimental randomized study

Abstract: Although epidemiologic research has demonstrated significant differences in incidence and outcomes of sepsis according to sex, their underlying biological mechanisms are poorly understood. Here, we studied the influence of hormonal status by comparing in vivo cardiac performances measured by MRI in non-ovariectomized and ovariectomized septic female rats. Control and ovariectomized rats were randomly allocated to the following groups: sham, sepsis and sepsis plus landiolol. Sepsis was induced by caecum ligatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…They also showed a survival advantage of female sex hormones against subsequent septic challenge [ 24 ]. In addition, less pronounced cardiac dysfunction was seen in female mice than in male mice in a cecal ligation and puncture (CLP) sepsis model [ 25 ]. In that study, female mice showed decreased production of TNF-α, IL-6, and inducible nitric oxide synthase.…”
Section: Different Effects Of Sex Hormones On the Outcomes Of Sepsis ...mentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed a survival advantage of female sex hormones against subsequent septic challenge [ 24 ]. In addition, less pronounced cardiac dysfunction was seen in female mice than in male mice in a cecal ligation and puncture (CLP) sepsis model [ 25 ]. In that study, female mice showed decreased production of TNF-α, IL-6, and inducible nitric oxide synthase.…”
Section: Different Effects Of Sex Hormones On the Outcomes Of Sepsis ...mentioning
confidence: 99%
“…Such effects were assumed to be due to overexpression of genes involved in calcium influx. In contrast, inactivation of the β-adrenergic and a calcium efflux pathway was seen in control females [ 25 ]. The protective effect of estrogen against liver damage in sepsis has also been observed in a lipopolysaccharide (LPS)-induced sepsis model.…”
Section: Different Effects Of Sex Hormones On the Outcomes Of Sepsis ...mentioning
confidence: 99%
“…Conversely, administration of landiolol increased calcium entry into the cardiomyocytes of ovariectomized female rats. Landiolol restored JAK2 expression and overexpressed genes responsible for calcium influx in ovariectomized septic females, whereas it did the opposite in control females [ 33 ]. This may explain why cardiac performance improves only in ovariectomized septic females (i.e., less exposure to female hormones during sepsis).…”
Section: Animal Modelsmentioning
confidence: 99%
“…Targeting of single proinflammatory mediators . The targeting of TNFα [ 215 ], IL1, IFNγ [ 125 , 126 , 127 , 136 , 137 ], proteases ( Section 5 [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]), and female sex hormones [ 413 , 415 , 445 ] has been tried and/or suggested by animal studies, but the results so far have not been convincing, even though IL1 inhibition and immunostimulation seemed to improve survival for subsets of sepsis patients in two of these studies [ 446 , 447 , 448 , 449 , 450 ].…”
Section: Therapeutic Targeting Of Neutrophils In Sepsis: Tried and Su...mentioning
confidence: 99%